Culture, worldview and transformative philosophy of mathematics education in Nepal: a cultural-philosophical inquiry - Luitel, Bal Chandra (Curtin University, 2009)
This thesis portrays my multifaceted and emergent inquiry into the protracted problem of culturally decontextualised mathematics education faced by students of Nepal, a culturally diverse country of south Asia with more than 90 language groups. I generated initial research questions on the basis of my history as a student of primary, secondary and university levels of education in Nepal, my Master’s research project, and my professional experiences as a teacher educator working in a university of Nepal between 2004 and 2006. Through an autobiographical excavation of my experiences of culturally decontextualised mathematics education, I came up with several emergent research questions, leading to six key themes of this inquiry: (i) hegemony of the unidimensional nature of mathematics as a body of pure knowledge, (ii) unhelpful dualisms in mathematics education, (iii) disempowering reductionisms in curricular and pedagogical aspects, (iv) narrowly conceived ‘logics’ that do not account for meaningful lifeworld-oriented thinking in mathematics teaching and learning, (v) uncritical attitudes towards the image of curriculum as a thing or object, and (vi) narrowly conceived notions of globalisation, foundationalism and mathematical language that give rise to a decontextualised mathematics teacher education program.With these research themes at my disposal my aim in this research was twofold. Primarily, I intended to explore, explain and interpret problems, issues and dilemmas arising from and embedded in the research questions. Such an epistemic activity of articulation was followed by envisioning, an act of imagining futures together with reflexivity, perspectival language and inclusive vision logics.In order to carry out both epistemic activities – articulating and envisioning – I employed a multi-paradigmatic research design space, taking on board mainly the paradigms of criticalism, postmodernism, interpretivism and integralism. The critical paradigm offered a critical outlook needed to identify the research problem, to reflect upon my experiences as a mathematics teacher and teacher educator, and to make my lifetime’s subjectivities transparent to readers, whereas the paradigm of postmodernism enabled me to construct multiple genres for cultivating different aspects of my experiences of culturally decontextualised mathematics education. The paradigm of interpretivism enabled me to employ emergence as the hallmark of my inquiry, and the paradigm of integralism acted as an inclusive meta-theory of the multi-paradigmatic design space for portraying my vision of an inclusive mathematics education in Nepal.Within this multi-paradigmatic design space, I chose autoethnography and small p philosophical inquiry as my methodological referents. Autoethnography helped generate the research text of my cultural-professional contexts, whereas small p philosophical inquiry enabled me to generate new knowledge via a host of innovative epistemologies that have the goal of deepening understanding of normal educational practices by examining them critically, identifying underpinning assumptions, and reconstructing them through scholarly interpretations and envisioning. Visions cultivated through this research include: (i) an inclusive and multidimensional image of the nature of mathematics as an im/pure knowledge system, (ii) the metaphors of thirdspace and dissolution for conceiving an inclusive mathematics education, (iii) a multilogical perspective for morphing the hegemony of reductionism-inspired mathematics education, (iv) an inclusive image of mathematics curriculum as montage that provides a basis for incorporating different knowledge systems in mathematics education, and (v) perspectives of glocalisation, healthy scepticism and multilevel contextualisation for constructing an inclusive mathematics teacher education program.